Handbook of solid-state lasers - Cheo, Peter K. (Optical engineering (Marcel Dekker, Inc.), 1989)
Provides information on both state-of-the-art technology and fundamental principles of fully developed solid-state lasers, emphasizing their operational characteristics and physical properties.